Critical potassium deficiency levels for a grass legume pasture grown on soils of the subhumid zone of Nigeria - Tening, A.S.; Tarawali, G.; Omueti, J.A.I. (Informa UK Limited, 1995)
A greenhouse experiment was conducted to determine the critical deficiency levels of potassium (K) in the subhumid zone soils for predicting response of a mixture of Andropogon gayanus and Stylosanthes hamata cVerano to K application. Twenty coarse textured soils, having loamy sand to sandy loam textures and with exchangeable K contents ranging from 0.08 to 0.97 cmol/kg, were used. Two rates of K applied were 0 and 80 mg k/kg. Application of K on soils testing less than 0.18 cmol/kg significantly increased the dry matter yields of both Andropogon and stylo tops. Soil K was significantly related to relative yields of Sole Andropogon (r=0.60**), sole stylo (r=0.78***), and Andropogon/stylo mixture (r=0.77***). There was a high correlation between the K concentration in plant tissue and the relative yields of sole Andropogon (r=0.68**), sole stylo (r=0.67**), Andropogon in mixture (r=0.65**), and stylo in mixture (r=0.64**). The graphical model of Gate and Nelson indicated the critical levels of the available form of K in soil to be 0.18, 0.20, and 0.21 cmol/kg for sole Andropogon, sole stylo and Andropogon/stylo mixture, respectively. The critical levels for K in plant tissues were also determined to be 1.30, 2.03, 1.38 and 1.86 percent for sole Andropogon, sole stylo Andropogon in mixture, and stylo in mixture, respectively.